Search for the Standard Model Higgs boson produced in association with a vector boson and decaying to a b-quark pair with the ATLAS detector - Castro, Nuno Filipe (2012)
This Letter presents the results of a direct search with the ATLAS detector at the LHC for a Standard Model Higgs boson of mass 110 <= m(H) <= 130 GeV produced in association with a W or Z boson and decaying to b (b) over bar. Three decay channels are considered: ZH -> l(+)l(-)b (b) over bar, WH -> lvbb (b) over bar and ZH -> v (v) over bar(b) over bar where l corresponds to an electron or a muon. No evidence for Higgs boson production is observed in a dataset of 7 TeV pp collisions corresponding to 4.7 fb(-1) of integrated luminosity collected by ATLAS in 2011. Exclusion limits on Higgs boson production, at the 95% confidence level, of 2.5 to 5.5 times the Standard Model cross section are obtained in the mass range 110-130 GeV. The expected exclusion limits range between 2.5 and 4.9 for the same mass interval.